Intestinal Atresia in Finland: Maternal Risk Factors, Prevalence, Associated Anomalies and Survival - Tahkola, Esko; Raitio, Arimatias; Helenius, Ilkka; Syvänen, Johanna; Kemppainen, Teemu; Löyttyniemi, Eliisa; Leinonen, Maarit K.; Gissler, Mika; Luoto, Topi; Pakarinen, Mikko P. (Wiley, 2026)
Aim: We aimed to investigate prevalence, associated anomalies and survival of congenital intestinal atresia and to examine maternal risk factors for jejunoileal atresia (JIA).
Methods: All children born with, or pregnancies terminated because of, JIA or colonic atresia (CA) in Finland during 1987-2019 were identified from the Finnish Register of Congenital Malformations. Clinical information was obtained from national health registers. Maternal risk factors were assessed using all JIA cases from 2004 to 2017 (n = 101). For each case, five appropriately matched live-born controls were selected.
Results: We identified 175 JIA and 48 CA cases. About half were isolated anomalies. Gastrointestinal anomalies were the most common associated defects (26% in JIA, 35% in CA), followed by cardiac anomalies in JIA (13%) and urinary tract anomalies in CA (19%). Survival was 88% in JIA and 94% in CA. Only two of 224 patients died directly due to intestinal atresia. Maternal insulin use (adjusted odds ratio [aOR] 8.4, 95% CI 1.4-51.0) and propionic acid derivatives (aOR 4.6, 95% CI 1.5-14.8) were associated with increased JIA risk.
Conclusion: Although associated anomalies were frequent, mortality in intestinal atresia remained low. Maternal insulin and propionic acid derivative use may meaningfully contribute to JIA risk.
Level of evidence: IV.